Quality Analysis of Crude Palm Oil (CPO) Processing and Proposed System Improvements to Increase Free Fatty Acid (FFA) Quality at PT. TLDN (CAP) - Bimbing Herwanto; Mahendrawathi ER (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2026)
Crude Palm Oil (CPO) is a strategic commodity whose quality and selling value are largely determined by the Free Fatty Acid (FFA) content. High FFA levels cause a decline in product quality and directly impact industry profitability. A CPO quality evaluation at PT. TLDN (CAP) demonstrated the inability of the production process to consistently produce premium CPO (FFA 3%). This study aims to identify the root causes of the increase in FFA in the CPO processing process and to formulate effective improvement strategies. The research method uses a quantitative approach with a case study, applying the Seven Tools of Quality to CPO production and quality data for March 2025. The analysis results show that the largest contribution to FFA formation comes from condensate and liquor flows with a cumulative contribution of 88%, while UnCO has a relatively stable FFA. Method factors are the dominant cause, especially mixing oil flows with different qualities in one storage tank, followed by machine and material factors. Improvement simulations through oil flow separation can reduce the FFA of premium products from 3.58% to 2.5-2.69% and increase the proportion of premium CPO to 37.44% without increasing production capacity. These results show that the integration of Seven Tools with oil flow separation effectively improves CPO quality while providing significant economic impacts